Iowa RBA, September 15, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for September 15, 1998. Highlights include Eurasian Collared Dove, Red-necked Phalarope, and Little Blue Heron. Includes notes for updates for September 18. Epson - sheet feed/flatbed